2015
DOI: 10.1038/nphys3377
|View full text |Cite
|
Sign up to set email alerts
|

Pressure is not a state function for generic active fluids

Abstract: Pressure is the mechanical force per unit area that a confined system exerts on its container. In thermal equilibrium, it depends only on bulk properties-such as density and temperature-through an equation of state. Here we show that in a wide class of active systems the pressure depends on the precise interactions between the active particles and the confining walls. In general, therefore, active fluids have no equation of state. Their mechanical pressure exhibits anomalous properties that defy the familiar t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

29
651
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 487 publications
(683 citation statements)
references
References 38 publications
29
651
1
2
Order By: Relevance
“…Indeed, a localized boundary orienting field was used by Solon et al (2015) to argue that the pressure of active matter is not a 'state' function, as the force per unit area on a wall is no longer equal to the swim pressure far from the surface. As our microscopic theory shows, this is to be expected in general: boundary curvature, the detailed flux conditions at the surface, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a localized boundary orienting field was used by Solon et al (2015) to argue that the pressure of active matter is not a 'state' function, as the force per unit area on a wall is no longer equal to the swim pressure far from the surface. As our microscopic theory shows, this is to be expected in general: boundary curvature, the detailed flux conditions at the surface, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, various formulas for P (involving, e.g., the density distribution near a wall [16], or correlators in the bulk [17,18]) are always equivalent. This ceases to be true, in general, for active particles [11,15].…”
mentioning
confidence: 99%
“…At first sight, because P can be defined mechanically as the force per unit area on a confining wall, its computation as a statistical average looks unproblematic. Remarkably, though, it was recently shown that for active matter the force on a wall can depend on details of the wall-particle interaction so that P is not, in general, a state function [15].…”
mentioning
confidence: 99%
See 2 more Smart Citations